CtMYB1 regulates flavonoid biosynthesis in safflower flower by binding the CAACCA elements - Yanxun Zhou; Jie Wang; Yanni Peng; Chao Chen; Bin Xian; Ziqing Xi; Chaoxiang Ren; Jin Pei; Jiang Chen (PLoS ONE, 2025)
Background Safflower ( Carthamus tinctorius L.) is a valuable herb known for its flowers, which are rich in flavonoids and are used for promoting blood circulation and preventing atherosclerosis. However, the molecular regulation of flavonoid biosynthesis in safflower is still poorly understood. In this study, we identified a AtMYB12 homologous gene, CtMYB1 , in safflower and characterized its sequence. The flower protoplast transient expression system and virus-induced gene silence (VIGS) technique were established in safflower and we tested the role of CtMYB1 in the regulation of flavonoid biosynthesis. The correlation between CtMYB1 and flavonoid synthesis genes was analyzed using a molecular interaction assay. Results Flower protoplasts transient expression showed that flavonoid biosynthesis genes CtC4H2 , CtF3H4 , and CtHCT12 were upregulated after transfection with CtMYB1 . Meanwhile, VIGS showed that the transfected petals were lighter in color, and there was a decrease in the amount of the major component Hydroxysafflor yellow A (HSYA) compared to the control. Yeast one-hybrid experiments demonstrate that CtMYB1 can bind to the promoters of flavonoid biosynthesis genes ( CtC4H2 , CtF3H4 ). The interaction analysis by the use of Biacore system revealed that CtMYB1 binds to the CAACCA element of flavonoid biosynthesis genes promoters. Conclusions CtMYB1 regulates flavonoid biosynthesis in safflower flower by binding the CAACCA elements of flavonoid biosynthesis related genes promoters, which sheds light on the molecular regulation of flavonoid biosynthesis in safflower. The flower protoplasts expression system and the VIGS system established in safflower are valuable tools for studying the function of genes involved in the regulation and biosynthesis of active compounds in safflower.